(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Corporate governance has emerged as a cornerstone of financial stability and ethical responsibility in India’s banking industry. This paper examines the evolution and current state of corporate governance in the Indian banking sector, integrating both conceptual insights and empirical evidence. Using aggregate data from public sector banks (PSBs) for the financial years 2019–20 to 2023–24, the study analyses key performance indicators such as return on assets, non-performing assets, capital adequacy, and profitability in relation to governance reforms implemented by the Reserve Bank of India (RBI) and the Ministry of Finance. The findings reveal that enhanced board oversight, stricter regulatory frameworks, and improved disclosure standards have strengthened the governance environment, reflected in improved profitability and reduced non-performing assets (NPA ratio down to 3.12 per cent in FY 2023–24). Nevertheless, challenges persist in maintaining board independence, risk culture, and accountability mechanisms in state-owned banks. The paper concludes by recommending further institutional reforms, capacity-building for directors, and greater digital transparency to align the sector with global governance standards.